Debt vs. revenue share financing: A theoretical study on revenue share finance in a capital-constrained newsvendor - Yufeng Song; Minghui Jiang (PLoS ONE, 2025)
In the capital-constrained newsvendor paradigm, revenue share financing (RSF) presents a novel yet underexplored financing approach. This theoretical study conducts a comparative analysis of two financing methods: traditional debt financing and revenue share financing. Our research findings indicate that the revenue share ratio, cost share ratio, and debt interest rate are the most critical factors influencing retailers’ decisions. This study further demonstrates that, under certain conditions, both financing strategies can yield competitive profit margins and order quantity. Additionally, we discovered that fund providers have a minimum revenue share ratio, whereas for retailers, there is a maximum revenue share ratio. These two ratios establish a bargaining interval within which an optimal revenue share ratio can be achieved if it falls within this range. Outside this range, RSF is either unattainable or impractical.